Evaluating the sit-to-stand transfer assistance from a smart walker in older adults with motor impairments - Werner, Christian; Geravand, Milad; Korondi, Péter Z.; Peer, Angelika; Bauer, Jürgen M.; Hauer, Klaus (Geriatrics and gerontology international, 2020)
Aim To evaluate the effectiveness and user satisfaction with the sit-to-stand (STS) assistance system of a smart walker (SW), and to identify factors associated with them in potential users. Methods A total of 33 older adults (29 women, aged ≥65 years) with motor impairments (habitual rollator use) and no severe cognitive impairment (Mini-Mental State Examination ≥17 points) carried out a Five-Chair Stand Test without assistance and five STS transfers with the STS assistance system. Based on the number of successfully completed STS transfers, success rates were calculated for the Five-Chair Stand Test and the SW-assisted STS transfers, and compared using the Wilcoxon signed-rank test. User satisfaction was assessed using the Tele-healthcare Satisfaction Questionnaire-Wearable Technology (0-80 points, higher score = higher satisfaction). Bivariate correlations and multiple linear regression analyses were used to identify participant characteristics associated with the success rate and user satisfaction with the STS assistance system. Results The success rate for the SW-assisted STS transfers was significantly higher than for the Five-Chair Stand Test (93.3 ± 12.9% vs 54.5 ± 50.6%, P < 0.001). User satisfaction was high (Tele-healthcare Satisfaction Questionnaire-Wearable Technology 62.5 ± 11.2 points). The success rate with the STS assistance system was not significantly associated with any participant characteristics. Higher body mass index was a significant independent predictor of higher user satisfaction. Conclusions The SW-integrated STS assistance system can provide effective STS support with high user satisfaction for a wide range of potential users. Our findings suggest the high potential of the STS assistance system for promoting mobility, independence and quality of life for older adults with motor impairments. Geriatr Gerontol Int 2020; 20: 312-316.